2021
DOI: 10.3390/drones5030068
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of Intelligent Inspection and Alarm Flight System for Epidemic Prevention

Abstract: Unmanned aerial vehicles (UAV) and related technologies have played an active role in the prevention and control of novel coronaviruses at home and abroad, especially in epidemic prevention, surveillance, and elimination. However, the existing UAVs have a single function, limited processing capacity, and poor interaction. To overcome these shortcomings, we designed an intelligent anti-epidemic patrol detection and warning flight system, which integrates UAV autonomous navigation, deep learning, intelligent voi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Because the current experimental new method of the Sun Yat-Sen University team is the first to propose RGBT-CC and use the dataset to complete the comparison of different fusion models, on the basis of this scheme, our method is improved and compared with experiments. We still use classical counting models such as MCNN [33], SANet [69], CSRNet [33], and Bayesian Loss [70] as the backbone networks for experimental reference. Compared with the best result of Bayesian Loss [70], our model has improved MAE and MSE by 0.54 and 0.53 on the RGBT-CC dataset.…”
Section: Density Regression Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the current experimental new method of the Sun Yat-Sen University team is the first to propose RGBT-CC and use the dataset to complete the comparison of different fusion models, on the basis of this scheme, our method is improved and compared with experiments. We still use classical counting models such as MCNN [33], SANet [69], CSRNet [33], and Bayesian Loss [70] as the backbone networks for experimental reference. Compared with the best result of Bayesian Loss [70], our model has improved MAE and MSE by 0.54 and 0.53 on the RGBT-CC dataset.…”
Section: Density Regression Methodmentioning
confidence: 99%
“…Similarly, our method is compared with multiple best-performing multimodal fusion models of UCNet [66], HDFNet [67], and BBSNet [68], and compared with the best-performing BBSNet [7], it is found that our model has 1.4 and 0.34 improvement in MAE and MSE on the RGBT-CC dataset. In the literature of the Sun Yat-Sen University team, the integration of the IADM "early fusion" mechanism into the classical counting model networks such as MCNN [33], SANet [69], CSRNet [33], and Bayesian Loss [70] can improve the performance of the model. e MAE and MSE of MCNN + IADM [33] have an improvement of 2.12 and 2.14; the MAE and MSE of SANet + IADM [33] have an improvement of 3.81 and 7.88; the MAE and MSE of CSRNet + IADM [33] have an improvement of 2.56 and 4.35; and the MAE and MSE of Bayesian Loss + IADM [33] have a 3.09 and 4.49 improvement.…”
Section: Density Regression Methodmentioning
confidence: 99%
“…NMANNED aerial vehicles (UAVs) have emerged as versatile and efficient tools in various application domains, such as aerial surveillance [1], target tracking [2], [3], and disaster response [4], [5]. A pivotal task within UAV systems is geo-localization, which estimates the geographic coordinates of drones in real time.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of research has focused on tracking objects in fixed or horizontally moving camera settings, such as handheld or vehicle-mounted cameras, with limited perceptual range. In recent years, unmanned aerial vehicles (UAVs) have gained widespread popularity in various domains, such as search and rescue, agriculture, sports analysis, and geographical surveying [6][7][8][9][10]. Multi-object tracking in airborne camera views faces more complex challenges than with fixed or horizontally moving cameras, such as small target sizes and fast camera movements [11,12].…”
Section: Introductionmentioning
confidence: 99%